The 'Compleat Physician' and Experimentation in Medicines: Everard Maynwaring (c.1629–1713) and the Restoration Debate on Medical Practice in London. Issue 2 (19th March 2018) - Barry, Jonathan
Abstract : Restoration London saw a wave of publications by physicians advocating that the 'compleat physician' should be one who experimented and produced his own medicines. Only thus, they argued, could the medical hierarchy be restored and medical authority re-established on a defensible basis. This article seeks to explain the context for this unusual approach, and why it failed to attract mainstream physicians by the end of the century, by considering the sixty-year career of one of its leading advocates, Everard Maynwaring ( c .1629–1713), a prolific medical author, and what his own failure to enter the medical establishment may show about the problems inherent in this model for the physician. A university-trained gentleman physician who converted to chymical medicine c .1660, Maynwaring published learned and relatively unpolemical texts to persuade both medical and lay audiences of the superiority of experimental medicine as a mode of learned practice, yet could not easily reconcile this with the advocacy and sale of his own chymical medicines (especially as he focused increasingly on a small group of 'universal medicines') without being branded an 'empirick'. Fragmentary evidence regarding his career suggests he became increasingly marginalised, and as an old man was reduced to advertising his cures like the 'empiricks' from whom he had sought to distance both himself and physicians in general.